Contextual research for educational improvement: A collaborative process in Northern California. (November 2019) - Baharav, Hadar; Newman, Elizabeth
Using an inquiry-based approach to address the challenge of improving schools provides opportunities for informed decision making and carries great promise for return on investment. Taking a collaborative approach toward improvement can be complex, yet also rewarding because of the opportunity to leverage the knowledge and capacity of multiple entities. The article presents an example of an education collaborative in Northern California that took an inquiry-based approach to their regional school improvement challenge of improving rates of college readiness and completion. The article provides insight into the structure, framework, and tools that were used to build and support the work of the collaborative, and reflects on the conditions that promote successful implementation of an inquiry-based approach to drive system change. Moreover, because each partner in the collaborative progressed through a unique process of inquiry and improvement, the article affords an opportunity to consider school improvement in multiple settings.